A multicentre randomised double masked clinical trial of a new formulation of topical cysteamine for the treatment of corneal cystine crystals in cystinosis. Issue 1 (1st January 2003) - Tsilou, E T; Thompson, D; Lindblad, A S; Reed, G F; Rubin, B; Gahl, W; Thoene, J; Del Monte, M; Schneider, J A; Granet, D B; Kaiser-Kupfer, M I
Abstract : Aim: To evaluate the safety and efficacy of a new topical cysteamine formulation, stable at room temperature, for the treatment of corneal cystine crystals in cystinosis. Methods: 20 study subjects were enrolled in the safety study and 16 in the efficacy study. Both studies were randomised and double blind. The primary outcome for the safety study was the occurrence of predefined serious adverse reactions over 6 months and for the efficacy study the reduction of corneal cystine crystal score (CCCS) by 1.00 or more units on photographs graded by a reading centre using a standardised protocol. Results: No study subject developed any serious adverse reactions. In the efficacy study, 47% of eyes receiving the standard formulation experienced a reduction in the CCCS of ≥1.00 after 1 year, while 7% of eyes on the new formulation experienced such a decrease (p=0.04). Conclusion: Although no serious adverse reactions were observed with either formulation, the new formulation was not as effective as the standard formulation.